Uso de inibidores da ACCase associados a mimetizadores de auxina no controle de milho GR voluntário - Bosqueiro, Rafael Orlandini (2021)
The control of voluntary GR corn is often performed using herbicides that inhibit the enzyme acetyl-Coenzyme A carboxylase (ACCase) and, in soybean crops resistant to dicamba and 2,4-D, care must be taken as associating graminicides with auxin mimics may result ein loss of afficiency of the graminicide. In this scenario, the size of the corn plant also influences the effectiveness of the product. Therefore, this study aimed to evaluate an association of haloxyfop-methyl and clethodim with 2,4-D and dicamba, in V4 and V6 corn stages. Two field trials were carried out, one when the corn was in V4 and the other one when it was in V6, both in a randomized block design with forty treatments each. Each experiment contained the herbicides haloxyfop-methyl at doses 30, 42 and 54 g a. e. ha-1 , clethodim at doses 72, 96 and 120 g a. i. ha-1 , 2,4-D at doses 670 and 1005 g a. e. ha-1 and dicamba at doses 480 and 720 g a. e. ha-1 , and the combination of each dose of each graminicide with each dose of each auxinic, in addition to a control treatment without application. Corn control percentage was evaluated at 5, 10, 15, 20, 25 and 30 days after applications (DAA), plant height at 0 and 30 DAA and plant dry mass at 30 DAA. The stem growth rate was calculated and the interaction between the herbicides was verified: synergistic, antagonistic or additive effects. The herbicides clethodim and haloxyfop-methyl report in isolate and the associations of clethodim with dicamba and 2,4-D, resulted in excellent control of corn in both stages of development. With corn in V4, the herbicide haloxyfop-methyl in association with dicamba showed 100% control. When associated with 2,4-D, low doses of haloxyfopmethyl resulted in control below 70%, while medium and high doses showed control above 90%. With corn in V6, an association with 2,4-D showed control values below 60%, much lower than the association with dicamba, which was less affected in all treatments. The results of plant height, shoot dry mass and stem growth rate showed a high proportionality ratio with the control values in all treatments in both stages of development, with treatments with high control values resulting in low plant height values, low growth rate and low values of shoot dry mass. Treatments with low control values resulted in high values of plant height, growth rate and shoot dry mass. According to the interaction analysis, all associations of clethodim with 2,4-D and dicamba were additive. Regarding haloxyfop-methyl, associations with dicamba in V4 were additive. The associations with 2,4-D in V4 and V6, and with dicamba in V6, were classified as antagonistic.